2022
DOI: 10.3390/polym14142889
|View full text |Cite
|
Sign up to set email alerts
|

Removal and Mechanism of Cadmium, Lead and Copper in Water by Functional Modification of Silkworm Excrement Biochar

Abstract: A new type of biochar, called GBC, was prepared from silkworm excrement, and then modified by chitosan combined with pyromellitic dianhydride. The removal of mono-metal and polymetals (Pb, Cd and Cu) from an aqueous solution by GBC was investigated in this research. Compared to unmodified biochar, the removal rate of Pb and Cd by GBC was about 12% higher, while that of Cu was about 94.6% higher. It also shows the types of functional groups in biochar have a great impact on their adsorption. The removal of Pb i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Modification increased the functional groups but decreased the mineral components, so the role of ion exchange and the precipitation mechanism in Pb removal were not significant; therefore, complexation played a dominant role. This counterbalancing effect is the reason adsorption did not significantly increase after modification [114].…”
Section: Pb(ii) Removal By Modified/functionalized Biocharmentioning
confidence: 92%
See 4 more Smart Citations
“…Modification increased the functional groups but decreased the mineral components, so the role of ion exchange and the precipitation mechanism in Pb removal were not significant; therefore, complexation played a dominant role. This counterbalancing effect is the reason adsorption did not significantly increase after modification [114].…”
Section: Pb(ii) Removal By Modified/functionalized Biocharmentioning
confidence: 92%
“…Therefore, both the kinetic and equilibrium behavior of the adsorption process are influenced by the extent of dispersion of magnetic particles on the biochar surface. Several other researchers [103,107,114,116,119] have investigated the comparative adsorption capacity between magnetic biosorbents and nanoparticle modifications and found that nanoparticles are less favorable for adsorption compared to magnetic biosorbents. This is partly due to the fact that magnetization causes a decrease in pHZPC, which reduces the difference between the pH and pHZPC.…”
Section: Pb(ii) Removal By Modified/functionalized Biocharmentioning
confidence: 99%
See 3 more Smart Citations